Strengthening Regional Water Security for Greater Resilience in the G5 Sahel - World Bank (World Bank, Washington, DC, 2021)
The World Bank’s historical engagement in transboundary water in West Africa is at a turning point, at a time when the G5 Sahel region faces unprecedented challenges. Therefore, it is time for the World Bank to broaden its water sector approach in the G5 Sahel and shift its focus to establishing a regional water security framework. The dual objectives of this report on the G5 Sahel region are to: (i) do a high-level analysis of water security challenges and their impacts on regional socio-economic development and stability, and (ii) suggest directions for future World Bank engagement on regional water security. The focus of this note is more exclusively on regional water challenges and local challenges with cross-border or even regional spillover effects. The report takes a development-driven approach to: (i) identify some of the ways in which water security affects socio-economic development in the G5 Sahel, (ii) explore the linkages between water security, resilience and conflict prevention, and (iii) present a set of guiding principles for the next regional engagements on water security in the region, both in terms of types of investment and implementation modalities. This report will also serve as a basis for deepening the dialogue with counterparts in the next fiscal year.